A Histological Study of Postnatal Development of Clavicle Articular Ends - Calixto, Luis Fernando; Department of Orthopaedic Surgery, School of Medicine, Universidad Nacional de Colombia, Bogotá, Colombia (2015)
The clavicle is the first bone to begin the process of ossification and the last one to complete it. Whilst histological studies of the clavicle have been focused mainly on embryonic events, our study focused on post natal clavicle development. The objective of this study was to perform a qualitative description of the clavicle’s epiphyseal growth to further shed light on the postnatal ossification process. Histological studies performed on clavicles obtained from cadavers confirmed medial and lateral extremities as true physes. Unlike the development of other long bones, no secondary ossification centre was present at the acromial end. Furthermore, appearance of the sternal end was observed after the age of 18, as evidenced in clavicles from a 19-year old individual. The articular surface of the clavicle’s acromial end was fibrocartilage. No histological studies have been performed before describing postnatal development of clavicular ends. Our data confirm the absence of an acromial secondary ossification centre, the late development of a secondary ossification centre at the sternal end, and the presence of fibrocartilage at the acromial end.